Structural, magnetic and x-ray absorption studies of NdCo 1-xNixO3 (0 ? x ? 0.5) - SHVETS, IGOR (My University, 2013)
We have systematically investigated the effect of Ni substitution on the structural and magnetic properties of NdCoO3. Single phase nature and orthorhombic Pbnm structure is confirmed by the Reitveld refinement of X-ray diffraction data in all samples. X-ray absorption near edge spectroscopy of Co and Ni K-edges reveals the presence of trivalent state of Ni and Co ions in all samples. Composition dependent crossover from canted antiferromagnetic (AFM) (for x<0.3) to spin glass behavior (for x 0.3) is observed in magnetic measurements. Low temperature ferromagnetic (FM) component in doped samples is attributed to the stabilization of Co?3 ions in intermediate-spin (IS) state t5 2ge1 g with S?1 The FM and AFM are observed to coexist as confirmed by M-H hysteresis. Nd sublattice seems to inhibit the magnetic contribution from Co ions, and we ruled out the possibility of charge disproportion induced by Ni substitution leading to FM interactions in these systems as proposed in different reports.VC 2013 American Institute of Physics.
PUBLISHED
Keywords: Physics